2017
DOI: 10.1016/j.cmet.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

FGF19, FGF21, and an FGFR1/β-Klotho-Activating Antibody Act on the Nervous System to Regulate Body Weight and Glycemia

Abstract: Despite their different physiologic functions as hormonal regulators of fed and fasted metabolism, pharmacologic administration of FGF19 and FGF21 similarly cause increases in energy expenditure, weight loss and enhanced insulin sensitivity in obese animals. Here, in genetic loss-of-function studies of the shared co-receptor β-Klotho, we show these pharmacologic effects are mediated through a common tissue-specific pathway. Surprisingly, FGF19 and FGF21 actions in liver and adipose tissue are not required for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
202
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(220 citation statements)
references
References 55 publications
15
202
1
2
Order By: Relevance
“…Protein restriction increases energy expenditure Earlier studies showed that FGF21 is required for low-protein-induced changes in energy expenditure, and that pharmacological FGF21 treatment acts in the brain and directly on adipose tissue to increase energy expenditure [3,6,12]. To test whether the energy expenditure might be different between the two low-protein groups despite a hyperphagic response, and explain the hyperglycaemia in LP/HC mice, energy expenditure was measured at the beginning and end of the study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein restriction increases energy expenditure Earlier studies showed that FGF21 is required for low-protein-induced changes in energy expenditure, and that pharmacological FGF21 treatment acts in the brain and directly on adipose tissue to increase energy expenditure [3,6,12]. To test whether the energy expenditure might be different between the two low-protein groups despite a hyperphagic response, and explain the hyperglycaemia in LP/HC mice, energy expenditure was measured at the beginning and end of the study.…”
Section: Resultsmentioning
confidence: 99%
“…Administration of FGF21 to mice induces activation of brown adipose tissue (BAT), and increases energy expenditure and insulin sensitivity [9][10][11]. The nervous system is the direct target of FGF21, whereas β-Klotho in adipose tissue and liver is dispensable for FGF21 effects on weight loss [12]. Furthermore, FGF21 improves beta cell function and survival [13], and prevents pancreatic inflammation [14].…”
Section: Introductionmentioning
confidence: 99%
“…The liver undergoes a postprandial metabolic reprogramming to assimilate the glucose and triggers liver–brain–periphery axis to turn off the fat utilization (Izumida et al , ). Hepatokine fibroblast growth factor 21 (FGF21) is a metabolic hormone induced by various metabolic stresses, including fasting, high‐carbohydrate diets and exercise that regulates energy homeostasis(Gaich et al , ; Galman et al , ; Kim et al , ,b; Lan et al , ; Solon‐Biet et al , ). The transgenic overexpression FGF21 mice showed female infertility and circadian behavior disruption (Bookout et al , ; Owen et al , ), and FGF21 treatment has also been shown to modulate the growth hormone, insulin‐like growth factor 1 (IGF1) axis, and stimulate bone loss (Talukdar et al , ; Wang et al , ; Wei et al , ; Zhang et al , ).…”
Section: Introductionmentioning
confidence: 99%
“…An interesting potential translational application to consider would be other causes of microvesicular steatosis, such as Reye syndrome or acute fatty liver of pregnancy; however, this speculation will require formal experimental validation. Further mouse studies have highlighted alternative pathways for FGF19 signaling in metabolic regulation by demonstrating that liver‐specific signaling is not required but rather that neuronal signaling mediates long‐term metabolic effects on body weight and glycemic control …”
Section: Role Of Fgf15 In Mouse Models Of Nafldmentioning
confidence: 99%